Developing Students’ Reading Comprehension Using STAD Strategy: A Classroom Action Research at SMA Negeri 7 Pekanbaru - Asmida Posmauli Marpaung; Indri Yanti; Yuliana Marzuki (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2019)
This study tries to explore the students’ improvement on reading comprehension and their results of completeness in learning using STAD type cooperative learning strategy. Using classroom action research (CAR), this study succeeded in finding out that the average score of the class in the first cycle using STAD was found reaching 51.42, while in the second cycle succeed with 74.28. The analysis of this study also reveals the percentage of student learning completeness in the first cycle test reached 21.43%, while the second cycle test managed to increase the score into 85.71%. The percentage of students' understanding in the first cycle showed only 51.42%, while in the second cycle extended into 74.28%. The analysis based on the observation sheet recorded on the first cycle reached 74.30%, while in the second cycle it increased into 91.66%. From The observation sheet for teacher, learning management in the first cycle recorded 84.17%, while in the second cycle it also increased into 90.47%. The data from observation sheet on group discussion in the first cycle managed also recorded 54.76%, while in the second cycle it showed a significant increasing into 90.47%. This study showed that students' reading comprehension has showing a significant increasing using the STAD Cooperative Learning Method in SMAN 7 Pekanbaru.